Homogenization of a quasilinear elliptic problem in domains with small holes. Issue 15 (13th October 2022) - Avila, Jake; Cabarrubias, Bituin
Abstract : This work aims to provide the asymptotic behavior of some class of quasilinear problems posed in a domain with small holes in R N for N >2, as ϵ → 0 . A nonlinear Robin boundary condition is prescribed on some of the holes, while a Dirichlet boundary one is imposed on the other holes as well as on the outer boundary. We apply the Periodic Unfolding Method for the homogenization of this problem.